4t+7-1=

Simple and best practice solution for 4t+7-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+7-1= equation:


Simplifying
4t + 7 + -1 = 0

Reorder the terms:
7 + -1 + 4t = 0

Combine like terms: 7 + -1 = 6
6 + 4t = 0

Solving
6 + 4t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 4t = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 4t = 0 + -6
4t = 0 + -6

Combine like terms: 0 + -6 = -6
4t = -6

Divide each side by '4'.
t = -1.5

Simplifying
t = -1.5

See similar equations:

| 4x+6=-44-6x | | 0=-7y+20 | | 6-4d=-6-9d | | 4(5x-3)=10x+8 | | 9m-7-4m= | | 9x^2+24x-22=0 | | 3+2n=-3 | | y=x^2+kx+100 | | 5x+3=3(x-3) | | 5x+42=2x+18 | | 32+2x=8x-16 | | 7x-68=9x-96 | | -12.19-0.5x=5.3(x+3.5) | | 7(3x+2)=3(x+2)-17 | | ln(x+3)-4=ln(x-5) | | 5+2(3y-1)=2y-5 | | 100x-4x^2=20 | | 4x^2-25x+14=-4x+9 | | 4v-24=8v | | 7(c+2.1)=14c-0.7 | | 56(7)= | | 1.5(y-10)=0.4-y | | 3x+21=48+2x | | -8=x-2y | | 14=p-8 | | 1/4t+1/3t=7/12 | | 0.05+0.01x=6x | | 2(x+3)=6x-12 | | 5(2x+3x)-20=55 | | 100-4x=20 | | 6x+3y=16 | | 100-4x= |

Equations solver categories